Comment II: Documentation of Torture and Justice ‘Bon pour L`Orient’i? - Özkalıpcı, Önder (Torture Journal, 2018)
The study by Kelly et al. on the Istanbul Protocol (IP) was made in three low-income countries. It is based on eighty interviews of human rights practitioners who in “many cases… were lawyers, but clinicians and other human rights professionals were also included.” (p63) The study does not provide a breakdown of the individuals interviewed, their professions, or their experience in documentation and specifically medico-legal or IP documentation. The study does not assume interviewees had any prior knowledge of the IP. In addition, health professionals – a key group that implements the IP – do not appear to be well represented among the interview group.